2016
DOI: 10.1155/2016/2081962
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Glutamine, Curcumin, and Nesfatin-1 on the Gastric Serosal Surface Neomucosa Formation: An Experimental Rodent Model

Abstract: Introduction. Short bowel syndrome can crop up if more than 50% of small intestine is resected or when less than 100 cm of small bowel is left. Glutamine is the main food source of enterocytes. Curcumin has protective effects on intestinal ischemia-reperfusion damage. Nesfatin-1 is a satiety molecule. It has protective effects on gastric mucosa. The primary purpose of this study is to compare effects of glutamine, curcumin, and nesfatin-1 on the gastric serosal surface neomucosa formation on rats. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…During serious depletion of glutamine stores in severe metabolic stress conditions such as trauma, sepsis, and inflammatory bowel disease, glutamine supplementation was evaluated as a remedy to improve the clinical outcomes. [5,10] Histopathological evaluation of rats treated with glutamine in the present study showed higher neomucosa formation in terms of numbers compared to the control group, but the difference was not significant (p=0.315) (Table 2 and Fig. 4).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…During serious depletion of glutamine stores in severe metabolic stress conditions such as trauma, sepsis, and inflammatory bowel disease, glutamine supplementation was evaluated as a remedy to improve the clinical outcomes. [5,10] Histopathological evaluation of rats treated with glutamine in the present study showed higher neomucosa formation in terms of numbers compared to the control group, but the difference was not significant (p=0.315) (Table 2 and Fig. 4).…”
Section: Discussionmentioning
confidence: 49%
“…These complex and specialized treatment modalities which necessitate specialized experience are associated with high morbidity and mortality rates even in the best centers. [5] SBS is one of the most common causes that require patients to receive long-term parenteral nutrition (PN). In the long run, PN can cause serious infections, venous thromboembolism, catheter malfunction, metabolic complications such as liver and kidney disease, and eventual organ failure and death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations